2009
DOI: 10.1038/aps.2009.30
|View full text |Cite
|
Sign up to set email alerts
|

Harm reduction for injecting opiate users: an update and implications in China

Abstract: The harm associated with high-risk injected opiate use and the threat of the HIV epidemic among injecting drug users has become a worldwide problem. Twenty years ago, in the face of a rapid increase in mortality rates among injecting drug users and the upcoming threat of HIV, the first harm-reduction programs were implemented in the Western world. This paper is a literature review describing four forms of harm reduction currently in use in Europe, North America, and Australia. Each represents a reasonable coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…MMT admission was restricted to opiate using local residents at least 18 years old (Meise et al, 2009; Tang et al, 2006a), and after 2006, admission did not require a history of failed prior detoxification attempts (Meise et al, 2009). Patients could miss medication without penalties and could resume treatment by simply returning to the clinic for treatment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…MMT admission was restricted to opiate using local residents at least 18 years old (Meise et al, 2009; Tang et al, 2006a), and after 2006, admission did not require a history of failed prior detoxification attempts (Meise et al, 2009). Patients could miss medication without penalties and could resume treatment by simply returning to the clinic for treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Problems with opiate use, injection drug use (IDU), and transmission of human immunodeficiency virus (HIV) are closely interrelated in China, which has an estimated 780,000 HIV infected individuals and over 2 million registered drug users (Kulsudjarit 2004; Lu and Wang, 2008; Meise et al, 2009; Ministry of Health of the People’s Republic of China, 2012; Narcotics Control Bureau of the Chinese Ministry of Public Security, 2013; Yin et al 2010). Injection of drugs is associated with 42% of HIV transmissions, and about 45% of people who inject drugs in China are estimated to share needles and injection equipment (Chu and Levy, 2005; Meise et al, 2009; Lu and Wang, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Building on existing community networks, trained peers assist PWID to access exchangers, distribute information about safer drug use and safer sex, and facilitate referrals to other user-friendly health services. Although not exempt of limitations and shortcomings (8), the peer service model, in addition to disseminating safer practices and making a variety of health services more accessible, emphasizes the importance of reconstructing relationships with family, friends, and the community at large (9, 10), which may ultimately contribute to promote greater psychological stability and enhance the benefits of psychiatric interventions. In the area of mental health, there is considerable theoretical and experiential support for the notion that peer support may exert a positive influence in multiple relevant domains, including empowerment (11), symptom distress (12), self-esteem (13), and social integration (14).…”
Section: Introductionmentioning
confidence: 99%
“…One study has shown that the probability of having an HIV infection was approximately 6 times greater among heroin addicts who had never received MMT as compared to heroin addicts in an MMT program [ 16 ]. In response to public health concerns about heroin use and heroin use-related HIV transmission, China’s Ministry of Health launched a national MMT program to provide methadone treatment to heroin addicts in communities [ 2 , 16 , 17 ]. In 2004, the first eight MMT clinics were opened in the southwestern China, and the program has since expanded to 748 clinics in 2012.…”
Section: Introductionmentioning
confidence: 99%